Successful weaning in a patient of post-tubercular sequalae with obstructive airway disease by leak valve - Kamran Chaudhary; Sahil Singh; Manas Kamal Sen; Shailly; Mona Jha (The Journal of Association of Chest Physicians)
A leak valve is intended to provide leak ventilation during positive pressure ventilation. This is an important way for patients to experience difficult or prolonged weaning. It is designed with an anti-asphyxia valve to allow for spontaneous breathing and prevent CO2 rebreathing figure 1. It also allows continuous airflow through the vent holes. We report a case of a 22-year-old female patient diagnosed with post-tubercular obstructive airway disease with hypercapnic respiratory failure discharged with tracheostomy with home oxygen and noninvasive ventilation support with leak valve after prolonged weaning in the intensive care unit.